2019
DOI: 10.1186/s12967-019-02144-7
|View full text |Cite
|
Sign up to set email alerts
|

BMI, irAE, and gene expression signatures associate with resistance to immune-checkpoint inhibition and outcomes in renal cell carcinoma

Abstract: BackgroundClinical variables may correlate with lack of response to treatment (primary resistance) or clinical benefit in patients with clear cell renal cell carcinoma (ccRCC) treated with anti-programmed death 1/ligand one antibodies.MethodsIn this multi-institutional collaboration, clinical characteristics of patients with primary resistance (defined as progression on initial computed tomography scan) were compared to patients with clinical benefit using Two sample t-test and Chi-square test (or Fisher’s Exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 65 publications
2
37
0
Order By: Relevance
“…Recent retrospective studies investigating Open access the effects of obesity on immunotherapy outcomes in RCC have provided intriguing but conflicting results: that increased adiposity (defined as BMI >25 kg/m 2 ) trended toward being detrimental, 18 that obesity (BMI >30 kg/m 2 ) had no impact on outcomes in multivariate analysis, 16 or that obesity improved PFS but not OS in patients who showed primary clinical benefit. 19 We examined this issue by evaluating outcome data for all RCC patients treated with standard of care anti-PD-1 who had ≥6 months of follow-up from treatment initiation at the UAB Hospital (n=54) and the UI Hospitals and Clinics (n=18). All patients had an ECOG performance status of 0-2 and none had received prior immunotherapies.…”
Section: Obesity Is Associated With Poorer Pfs and Os In Metastatic Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent retrospective studies investigating Open access the effects of obesity on immunotherapy outcomes in RCC have provided intriguing but conflicting results: that increased adiposity (defined as BMI >25 kg/m 2 ) trended toward being detrimental, 18 that obesity (BMI >30 kg/m 2 ) had no impact on outcomes in multivariate analysis, 16 or that obesity improved PFS but not OS in patients who showed primary clinical benefit. 19 We examined this issue by evaluating outcome data for all RCC patients treated with standard of care anti-PD-1 who had ≥6 months of follow-up from treatment initiation at the UAB Hospital (n=54) and the UI Hospitals and Clinics (n=18). All patients had an ECOG performance status of 0-2 and none had received prior immunotherapies.…”
Section: Obesity Is Associated With Poorer Pfs and Os In Metastatic Rmentioning
confidence: 99%
“… 18 However, another 2019 study of 90 RCC patients reported no difference in BMI status between patients who derived clinical benefit from anti-PD-1/PD-L1 versus those who were resistant to therapy. 19 A third study found that in RCC patients (n=203) treated with immunotherapy (any monotherapy or combination of anti-PD-1/PD-L1/CTLA-4 during clinical trials or standard of care), obesity did not alter immune infiltration or improve survival after adjusting for risk score, but instead decreased PD-L1 expression and increased angiogenesis in renal tumors. 16 Thus, further investigation of this critical issue is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 27 studies were subsequently reviewed and screened according to our inclusion and exclusion criteria. Finally, 13 studies [13][14][15][16][17][23][24][25][26][27][28][29][30] were included in our meta-analysis ( Fig. 1).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…The diagnosed cancer types of these patients were mainly non-small cell lung cancer (NSCLC) (68.2%), melanoma (18.5%), and renal cell carcinoma (10.2%). With regard to BMI values, seven studies [13, 15-17, 24, 25, 28] stratified the BMI value into high BMI group and low BMI group by one cutoff value, four studies [14,23,27,29] stratified the BMI values into normal BMI group (18.5 < BMI ≤ 24.9), overweight group (25.0 < BMI ≤ 29.9) and obese group (BMI ≥ 30) according to the WHO definition, one study [26] used both two methods to stratify BMI value. Notably, one study [30] stratifies BMI into 3 groups (BMI < 25, 25.0 ≤ BMI < 35, BMI ≥ 35), which was neither dichotomous nor stratifying BMI into normal overweight and obese groups.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…As a contradiction, an inverse trend was reported by Bergerot et al [71], where a small group of immunotherapy-treated metastatic RCC patients with low BMI had a median OS of 23.6 months compared to 19.9 months in overweight/obese patients. A study by Labadie et al [72] reported that BMI was not correlated with OS in ccRCC patients with primary resistance to immunotherapy, while the correlation was positive in immunotherapy-sensitive patients.…”
Section: Introductionmentioning
confidence: 99%